Interpretasi Film Budi Pekerti: Antara Moral Dan Viral (International Forum of Researchers and Lecturers, 2024)
The development of the world of cinema is currently growing rapidly, including in Indonesia. Various film themes have been produced as a means of entertainment and conveying messages to audiences. This research aims to describe the message conveyed in a film by analyzing the content qualitatively in the presentation of the story of the film